ANALISIS STRATEGI FUNDRAISING DAN PELAKSANAAN PROGRAM LAZNAS (LEMBAGA AMIL ZAKAT NASIONAL) YATIM MANDIRI DI ERA NEW NORMAL (Studi Kasus Cabang Yatim Mandiri Solo) - Lili Aisyah; Rindiani; Rahmawati; Susilowati (ICO EDUSHA, 2021)
Throughout the beginning of 2020 until now, the Covid-19 pandemic has had a wide impact on the global health and economic crisis. The Indonesian government enacted the PSBB policy which was then followed by a new policy, namely the New Normal policy, where community activities are restricted and have a large impact on their social activities, especially the impact of work and economy. Likewise, the impact experienced by LAZNAS Yatim Mandiri in the fundraising process experienced obstacles such as payment of bad donors, donors came out as permanent donors of Yatim Mandiri and some obstacles in the sustainability of the program. In this journal will be discussed how the analysis of fundraising strategies and the implementation of the LAZNAS Yatim Mandiri program in the Solo Branch. This study uses qualitative approaches with observation methods, interviews and literature methods. The data used comes from primary and secondary data. The results showed that although the pandemic had an impact that greatly affected the activities of the community and institutions, but LAZNAS Yatim Mandiri has a solution in the form of a strategy that continues to be developed both in terms of the fundraising team and all existing programs to continue running and realized properly so that mustahik will still get its rights from muzaki through Yatim Mandiri. Keywords: Fundraising , LAZNAS Yatim Mandiri and New Normal References Arianda, Aditia. 2021. COVID-19 : Epidemiologi, Virologi, Penularan, Gejala Klinis, Diagnosa, Tatalaksana, Faktor Risiko Dan Pencegahan. Jurnal Penelitian Perawat Profesional, Vol. 3 Assuari, Sofjan. 2014. Manajemen Fundraising. Jakarta: Raja Grafindo Persada. Coryna IA, Tanjung H, Formulasi Strategi Penghimpunan Zakat. Jurnal Al-Muzara’ah Iamulloh. 2013. Metode Fundraising Dana Zakat, Infak dan Sedekah pada Badan Amil Zakat Daerah (Bazda) Kabupaten Sukabumi. EMPATI: Jurnal Ilmu Kesejahteraan Sosial Vol. 2 Fakhruddin. 2008. Fiqh dan Manajemen Zakat di Indonesia. Malang: UIN-Malang Press https://www.yatimmandiri.org/ di akses pada 22 Juli 2021 pukul 05.38 Khasanah, Umrotul. Manajemen Zakat Modern Instrumen Pemberdayaan Ekonomi Umat. Malang: UIN Maliki Press. Muhyiddin. 2020. Covid-19, New Normal dan Perencanaan Pembangunan di Indonesia. The Journal of Development Planning. Vol. IV Nopiardo, Widi. 2015. STRATEGI FUNDRAISING DANA ZAKAT PADA BAZNAS KABUPATEN TANAH DATAR. Jurnal Imara Rai’udin dan Djalil, Manna Abdul, 1997. Prinsip dan Strategi Dakwah,Bandung: Pustaka Setia. Rahmatina, A. Kasri. 2018. Fundraising Strategies to Optimize Zakah Potential in Indonesia: An Exploratory Qualitative Study. Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah (Journal of Islamic Economics). Vol.1 Rosyidah, Muallimatur. 2019. STRATEGI MARKETING MIX PADA LEMBAGA AMIL ZAKAT NASIONAL YAYASAN YATIM MANDIRI SIDOARJO. Sudirman.2007. Zakat dalam Pusaran Arus Modernitas (Malang: UIN-Malang Press) Undang-Undang Nomor 23 Tahun 2011 tentang Pengelolaan Zakat Lembaran Negara Tahun 2011 Nomor 115 Undang-Undang Nomor 38 Tahun 1999 tentang Pengelolaan Zakat Lembaran Negara Tahun 1999 Nomor 164 Tambahan Lembaran Negara Nomor 3885